2004
DOI: 10.1111/j.0021-8782.2004.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and species differences in gastric ghrelin cells from mice, rats and hamsters

Abstract: Ghrelin is a newly identified gastric peptide hormone that has various important functions, including growth-hormone release and appetite stimulation. Ghrelin-immunoreactive cells (ghrelin cells) are characterized by X-type endocrine cells in the rat stomach. In the present study, we analysed ghrelin cells in fundi of stomach from ICR mice and Syrian hamsters immunohistochemically, immunoelectron microscopically and morphometrically, and compared the results with those from Wistar rats. Immunohistochemistry re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…Since tryptase is wellknown marker for MCs [52], we performed double immunofluroescent staining for ghrelin with tryptase to confirm that both CTMCs and MMCs express ghrelin (Figure 1(a,b) (Figure 2(a-c)). This finding allowed us to suggest that MCs are another cell type within the rat gastric wall capable to produce ghrelin similarly to A/X cells [31,32,34]. [49] who reported that toluidine blue is a universal marker for all MCs [49].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Since tryptase is wellknown marker for MCs [52], we performed double immunofluroescent staining for ghrelin with tryptase to confirm that both CTMCs and MMCs express ghrelin (Figure 1(a,b) (Figure 2(a-c)). This finding allowed us to suggest that MCs are another cell type within the rat gastric wall capable to produce ghrelin similarly to A/X cells [31,32,34]. [49] who reported that toluidine blue is a universal marker for all MCs [49].…”
Section: Resultsmentioning
confidence: 97%
“…[27][28][29][30][31][32][33][34][35][36][37][38][39][40]41] Ghrelin is known to be an endogenous ligand for the growth hormone secretagogue receptor (GHS-R) 1a, capable of stimulating growth hormone release from the pituitary gland. This peptide hormone has been obtained from rat and human stomachs [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ghrelin-containing cells are a distinct endocrine cell type found in the mucosal layer of the stomach and are more abundant in the fundus than in the pylorus (Date et al, 2000;Rindi et al, 2002;Yabuki et al, 2004). Four different types of endocrine cells have been identified in the stomach mucosa: ECL, D, enterochromaffin (EC), and X/A-like cells (Davis, 1954;Capella et al, 1969;Solcia et al, 1975).…”
Section: Ghrelin In the Stomachmentioning
confidence: 99%
“…Four different types of endocrine cells have been identified in the stomach mucosa: ECL, D, enterochromaffin (EC), and X/A-like cells (Davis, 1954;Capella et al, 1969;Solcia et al, 1975). The X/A-like cells contain compact, round, electron-dense granules that are filled with ghrelin (Date et al, 2000;Dornonville de la Cour et al, 2001;Yabuki et al, 2004). In adult oxyntic glands, the X/A-like cells account for approximately 20% of the endocrine cell population.…”
Section: Ghrelin In the Stomachmentioning
confidence: 99%